A Vilnius Transcript of the Health Garden: A Codicological Study - Cicėnienė, Rima (Knygotyra, 2021)
This article is devoted to the history of cultural relations between the Grand Duchy of Lithuania and Moscovian Rus’ as well as the artifacts that testify to it. The object of the research is a Vilnius transcript of the Health Garden (a translation of Gart der Gesundheit (1492) into Russian) kept in the Wróblewski Library of the Lithuanian Academy of Sciences (LMAVB RS F22–25). The aim of the article is to present a revised codicological description of the object, identifying the features of the Vilnius transcript and its links with the culture of the Grand Duchy of Lithuania. This aim is achieved by using codicological, comparative and textual methods, compiling a detailed codicological description of the copy, analyzing the architecture and internal structures of the code, and identifying differences or similarities between the Vilnius, Flor, Uvarov, and Shelonin copies of the Health Garden. Based on the gathered data, the circumstances of compiling the code are clarified. The study identified the following features of the Code. The large-scale codex, created in Moscow between the 17th and 18th centuries, is not a homogeneous object. It consists of two different editions: the index is closer to the Uvarov transcript and the main text to the Kharkov / Flor transcript. The second feature is careful preparation of the transcript. The codex was drafted as an exemplary edition of an old manuscript and is richly illustrated. Colored pigments were used for decoration, leaving traces of gilding. The edges of the Codex block were painted and decorated in ornamental prints. This allows us to consider the high social status of the client of the code. The third feature is the completeness of the text of the Vilnius copy. It consists of the most comprehensive block of indexes; the main text has been supplemented with new objects, enriched with new images; the text contains as many as 237 names of medicinal substances and 38 minerals in Russian. The remarks and additions contained in the previous transcripts became an integral part of the texts of the Vilnius transcript. The identified features, overlapping formal features, and organization scheme of the text, as well as the same manner of illustration, gave reason to search for a place where all the mentioned copies – Flor, Uvarov, Shelonin – as well as other old prints or their translations could have been seen by the creators of the Vilnius transcript. It is believed that such a place could have been the The Apothecary Chancery. Some Polonisms are found in the text; the works of authors from the Polish-Lithuanian Commonwealth were used in the Rus’ at that time and thus encourage a closer look at the translations and the search for citizens from the Polish-Lithuanian Commonwealth who could have participated in the works. The research clarifies the available knowledge about the transcript kept in Vilnius. The information gathered is expected to help book historians clarify the origin of the codex, its production environment, and its place in the Gart der Gesundheit’s line of translations and transcripts; this paper will make it possible to identify other stored fragments. The article is supplemented with a comparative table of the structure and content of the Vilnius transcript of the Health Garden and a decor picture of the code block.